PENDAMPINGAN ASISTENSI PENGISIAN SPT TAHUNAN BAGI DOSEN DAN KARYAWAN UNIVERSITAS BHAYANGKARA SURABAYA - Yoga Adi Prayogi; Ruchan Sanusi; Arief Rahman; Dien Ajeng Fauziah; Ali Muhdor; Bambang Agoes Hermanto (Jubaedah : Jurnal Pengabdian dan Edukasi Sekolah (Indonesian Journal of Community Services and School Education), 2024)
The completion and submission of the Annual Income Tax Return for Individual Taxpayers requires particular attention from taxpayers who are employed in an agency. As a taxpayer is obliged to calculate, deposit taxes, and complete and submit the Annual Income Tax Return for Individual Taxpayers no later than March 31 of the following year. The objective of this community service (PKM) initiative is to provide assistance to lecturers, educators, and employees of Bhayangkara University Surabaya in the completion and submission of the Annual Income Tax Return for Individual Taxpayers, specifically the SPT 1770SS and 1770S forms, through the electronic filing (e-filing) process. This initiative aims to provide solutions for lecturers, educators, and employees at Bhayangkara University Surabaya to fulfill their obligations as individual taxpayers. The methodology employed in this activity entails providing assistance in the completion and submission of the Annual Income Tax Return for Individual Taxpayers through the use of electronic filing. The implementation of this activity represents a collaborative effort between the Tax Center UBHARA Surabaya and the KPP Pratama Surabaya Wonocolo, with the involvement of students from the Tax Volunteers for the Country (Renjani) program, who have been duly authorized by the Directorate General of Taxes Ministry of Finance RI